2004
DOI: 10.17796/jcpd.28.3.2554xv412644ru13
|View full text |Cite
|
Sign up to set email alerts
|

A simplified technique for the restoration of severely mutilated primary anterior teeth

Abstract: The restoration of severely carious primary anterior teeth is a challenge to the pediatric dentist. The introduction of new materials and technologies makes re-evaluation of existing treatment philosophies necessary.A technique involving the placement of an omega shaped stainless steel wire extension into the entrance of the root canal prior to restoring the crown with a compomer material is described. 96 restorations were placed in 25 children. After 18 months 81.2% of the 96 restorations, which were availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 13 publications
0
51
0
4
Order By: Relevance
“…The results of various studies have demonstrated that short-post cores and over restorations can be used to treat such patients 3,[7][8][9] . Initially, pins or orthodontic wires combined with composite resin were used in the short-post core technique prior to over restorations with polycarbonate crowns 6,10) . With the advent of new adhesive materials and techniques, different composite resin short posts and fiber-reinforced composite resin short posts have been available for the restoration of severely decayed primary anterior teeth 7,11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…The results of various studies have demonstrated that short-post cores and over restorations can be used to treat such patients 3,[7][8][9] . Initially, pins or orthodontic wires combined with composite resin were used in the short-post core technique prior to over restorations with polycarbonate crowns 6,10) . With the advent of new adhesive materials and techniques, different composite resin short posts and fiber-reinforced composite resin short posts have been available for the restoration of severely decayed primary anterior teeth 7,11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of primary incisors is often a difficult procedure that presents a special challenge to dental surgeons and to the pediatric dentist (17,18). The esthetic restoration of severely decayed primary anterior teeth has for a long time been a challenge for the pediatric dentist, not only because of the available materials and techniques, but also the children who require such restorations are usually among the youngest and least manageable group of patients (6).…”
Section: Discussionmentioning
confidence: 99%
“…Restauracija mliječnih sjekutića često je težak postupak i zato predstavlja poseban izazov oralnim kirurzima i dječjim stomatolozima (17,18). Estetska restauracija teško oštećenih prednjih mliječnih zuba dugo je bila izazov dječjim stomatolozima, ne samo zbog materijala i tehnika, nego i zato što se djeca kojima je potrebna ubrajaju u skupinu najmlađih i najtežih pacijenata za suradnju (6).…”
Section: Raspravaunclassified
See 2 more Smart Citations